Z-Score Analysis as a Tool for Predicting Financial Distress in Insurance Sector Companies Listed on the Indonesia Stock Exchange - Aswirah; Imaduddin, Imaduddin (Newinera Publisher, 2024)
This study aims to analyze the application of the Altman Z-Score model in predicting financial distress in insurance sector companies listed on the Indonesia Stock Exchange for the 2020-2022 period. The research utilized secondary data from the financial statements of nine companies selected through purposive sampling. Data analysis was conducted by calculating financial ratios and interpreting Z-Scores to classify the financial condition of companies into healthy, gray, or distressed categories. The findings revealed that companies like ABDA and AMAG consistently fell within the healthy category, indicating stable financial management. Conversely, companies like MTWI experienced significant financial declines with negative Z-Scores, indicating a high risk of bankruptcy. Other companies fell in the gray area with opportunities for improvement through enhanced profitability and capital management. The conclusion highlights the effectiveness of Altman Z-Score as a predictive tool, capable of providing early warnings about financial risks in Indonesia’s insurance sector.